EFIKASI DIRI BERHUBUNGAN DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS: SELF-EFFICIENCY RELATED TO QUALITY OF LIFE OF CHRONIC KIDNEY FAILURE PATIENTS THAT ARE TAKING HEMODIALYSIS - Wa Ode Sri Asnaniar; Sitti Zubaedah Bakhtiar; Safruddin Safruddin (Akademi Keperawatan Yarsi Samarinda, 2020)
Patients with chronic kidney failure lose kidney function so the body loses its ability to maintain metabolism, fluid and electrolyte balance. This causes physical problems in patients due to illnesses experienced, such as shortness, edema, anorexia and so forth. Patients not only experience physical problems, but psychological problems that can affect the decline in the quality of life of patients. One factor that can optimize the quality of life of patients undergoing hemodialysis is self-efficacy. This study aims to determine the relationship of self-efficacy with the quality of life of patients with chronic kidney failure undergoing hemodialysis at the Hospital in Makassar City. The study design uses analytic surveys using a cross-sectional approach. Sampling in this study used a total sampling technique with a sample size of 30 respondents using the Chi-Square statistical test with a significance level α less than 0.05. Statistical test results showed that of 30 patients, there were 20 patients who had high self-efficacy and good quality of life, and from 10 patients who had low self-efficacy there were 1 (10%) people who had good quality of life and 9 (90 %) people have a poor quality of life with a value of ρ = 0,000 (ρ less than 0.05) which means there is a relationship between self-efficacy and the quality of life of patients with chronic kidney failure undergoing hemodialysis.